Investigation of the Relationship between Leadership Orientations, Emotional Intelligence Levels and Decision Making Styles of Manager Candidates - Mücahit DURSUN; Mehmet GÜNAY (Sportif Bakış Spor ve Eğitim Bilimleri Dergisi)
This study aimed to investigate the correlation between leadership orientations, emotional intelligence levels of administrator candidates, and their decision-making styles. The research group consists of 909 university students, comprising 470 females and 439 males, who are enrolled in various departments of State Universities in Ankara during the 2020-2021 academic year. The study utilized the following data collection tools: The "Multidimensional Leadership Orientations Scale (MLOS)" was created by Dursun, Günay, and Yenel (2019) to assess the leadership orientations of participants. To measure emotional intelligence levels, the "Trait Emotional Intelligence Questionnaire Short Form (TEIQue-SF)" developed by Petrides and Furnham (2000, 2001) was adapted to Turkish by Deniz, Özer, and Işık (2013). Additionally, decision-making styles were measured using the approach developed by Mann et al. The Melbourne Decision Making Questionnaire (MDMQ), originally developed by (1998), was utilized and later adapted into Turkish by Deniz (2004). When analyzing the data, we employed descriptive statistics as well as advanced statistical techniques such as Independent-Samples T-Test, One-Way Multivariate Analysis of Variance, Pearson Moments Multiplication Correlation, Simple Linear Regression, and Multiple Linear Regression analysis. The analysis revealed a notable disparity between the scores obtained from the leadership orientations and emotional intelligence scale and the variable of engaging in licensed sports. Ultimately, it was concluded that the leadership orientations and emotional intelligence levels of managers impact their decision-making styles.